1954
DOI: 10.1071/ch9540123
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Macrozamin in the seeds of Cycads

Abstract: CYCADS* Macrozamin was shown by Cooper (1940) to be the toxic principle of Macroxamia spiralis Miq., a New South Wales cycad. It was later obtained from the Western Australian M. reidlei C. A. Gard. (Lythgoe and Riggs 1949) and shown to be I or I1 (Langley, Lythgoe, and Riggs 1951).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1958
1958
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…It is not clear how S-nitrosation of Cys-␤93 increases the oxygen affinity on a molecular level. Although blocking this residue by alkylation has similar effects on the oxygen affinity, these data also show that unlike S-nitrosation, maximal increases in the oxygen affinity are only attained after both Cys-␤93 residues are blocked by N-ethylmaleimide (24).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…It is not clear how S-nitrosation of Cys-␤93 increases the oxygen affinity on a molecular level. Although blocking this residue by alkylation has similar effects on the oxygen affinity, these data also show that unlike S-nitrosation, maximal increases in the oxygen affinity are only attained after both Cys-␤93 residues are blocked by N-ethylmaleimide (24).…”
mentioning
confidence: 74%
“…However, since the hypothesis requires that only the deoxygenated conformer of Hb release NO (13,14), then the oxygen affinity of SNO-Hb (despite its low concentration) is critical to the role of Hb as an NO carrier. This is an important issue because previous studies on the role of Cys-␤93 have shown that blockage of the thiol via alkylation or the formation of mixed disulfides increases the oxygen affinity of Hb (24,25). Furthermore, the naturally occurring Hb variant Hb Okazaki, where Cys-␤93 is substituted with an arginine residue, also has an increased oxygen affinity (26).…”
mentioning
confidence: 99%
“…In addition to modifying the thiol residues of hemoglobin, NEM modification of the ␤93 cysteinyl residue also stabilizes hemoglobin in the so-called "R"-state or high oxygen-affinity state (11). The rates of GSNO decay and GSH formation were slightly faster when NEM-treated hemoglobin was used, suggesting that the kinetics of this reaction are related to the conformation of the hemoglobin tetramer.…”
Section: Methodsmentioning
confidence: 96%
“…Early studies by Riggs demonstrated that covalent modification of thiols in human and horse hemoglobin results in increased affinity of hemoglobin to O 2 and that oxygen binding results in increased thiol reactivity, which in human hemoglobin occurs on the ␤ chains (30,31). Nitrosation is another form of covalent thiol modification, and so it is not surprising that, like alkylation, nitrosative reactivity of the cys␤93 would be affected by the allosterically controlled exposure of the thiol residue, as demonstrated by Jia et al (5).…”
Section: Discussionmentioning
confidence: 99%